Study of common quantification methods of amide proton transfer magnetic resonance imaging for ischemic stroke detection. Issue 4 (26th October 2020) - Foo, Lee Sze; Larkin, James R.; Sutherland, Brad A.; Ray, Kevin J.; Yap, Wun‐She; Hum, Yan Chai; Lai, Khin Wee; Manan, Hanani Abdul; Sibson, Nicola R.; Tee, Yee Kai
Abstract : Purpose: To assess the correlation and differences between common amide proton transfer (APT) quantification methods in the diagnosis of ischemic stroke. Methods: Five APT quantification methods, including asymmetry analysis and its variants as well as two Lorentzian model‐based methods, were applied to data acquired from six rats that underwent middle cerebral artery occlusion scanned at 9.4T. Diffusion and perfusion‐weighted images, and water relaxation time maps were also acquired to study the relationship of these conventional imaging modalities with the different APT quantification methods. Results: The APT ischemic area estimates had varying sizes (Jaccard index: 0.544 ≤ J ≤ 0.971) and had varying correlations in their distributions (Pearson correlation coefficient: 0.104 ≤ r ≤ 0.995), revealing discrepancies in the quantified ischemic areas. The Lorentzian methods produced the highest contrast‐to‐noise ratios (CNRs; 1.427 ≤ CNR ≤ 2.002), but generated APT ischemic areas that were comparable in size to the cerebral blood flow (CBF) deficit areas; asymmetry analysis and its variants produced APT ischemic areas that were smaller than the CBF deficit areas but larger than the apparent diffusion coefficient deficit areas, though having lower CNRs (0.561 ≤ CNR ≤ 1.083). Conclusion: There is a need to further investigate the accuracy and correlation of each quantification method with the pathophysiology using a larger scale multi‐imaging modality and multi‐time‐point clinical study. Future studies should include the magnetization transfer ratio asymmetry results alongside the findings of the study to facilitate the comparison of results between different centers and also the published literature.